Google earth and teaching of cartography: a look at the new geotechnologies at the Santo Afonso Rodriguez School, Teresina municipality, state of Piaui - Sousa, Luciano Mascarenhas da Silva; Albuquerque, Emanuel Lindemberg Silva (Geosaberes; Vol 8 No 15 (2017): May - Aug, 2017)
The above study deals with the proposed implementation of geotechnologies, through Google Earth, at the Santo Afonso Rodriguez School, in the city of Teresina, state of Piauí. The research was carried out with 2nd year high school students during the second half of 2016. The overall objective was to highlight Google Earth as a geotechnological tool for teaching cartography. In this sense, we worked, methodologically, with the tools available in this platform with the concepts of scale, legend, coordinates and interpretation of orbital images. A questionnaire was applied to identify if the students were able to understand the concepts worked in practice. It was verified that the use of the tool used potentiates teaching and learning, with an emphasis on cartographic concepts.
Keywords: Geografia; Informática; Tecnologia